ARM Based Intelligent Soft Starter for Consumer Applications - Gowtham, M.; Vidhya, K. (Asian Journal of Electrical Sciences, 2015)
The main objective of this project is to design a soft starter for consumer application, Gsm technology is used to get the voltage readings through mobile, The power theft also identified here by means of voltage measurement is presented in this paper. Here thyristor is used as soft switch. Three soft switches are used in three phases which is Star, Delta and Main phase. With the help of Gsm technology the motor is controlled through the mobile. The performance resulted from the past fault-tolerant soft starter control has demonstrated reduced motor starting transient torque pulsations as well as reduced motor inrush current magnitude. The present are soft starter for consumer application presented here to demonstrate the soundness and effectiveness of the soft starter for consumer approach and motor can be controlled from remote location.